2004
DOI: 10.1074/jbc.m312645200
|View full text |Cite
|
Sign up to set email alerts
|

HIP1 and HIP1r Stabilize Receptor Tyrosine Kinases and Bind 3-Phosphoinositides via Epsin N-terminal Homology Domains

Abstract: Huntingtin-interacting protein 1-related (HIP1r) is the only known mammalian relative of huntingtin-interacting protein 1 (HIP1), a protein that transforms fibroblasts via undefined mechanisms. Here we demonstrate that both HIP1r and HIP1 bind inositol lipids via their epsin N-terminal homology (ENTH) domains. In contrast to other ENTH domain-containing proteins, lipid binding is preferential to the 3-phosphate-containing inositol lipids, phosphatidylinositol 3,4-bisphosphate and phosphatidylinositol 3,5-bisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 43 publications
2
78
1
Order By: Relevance
“…Interestingly, these truncated fusion proteins displayed a higher specific binding to PtdIns(3)P than to polyphosphorylated inositol lipids. On the other hand, our previous studies using the full-length HIP1 expressed in 293T cells indicated that its lipid-binding preference was polyphosphorylated 3-phosphoinositides (29). Our contradictory results may be due to either the absence of the carboxyl terminal end of the protein, differences in proteins expressed in bacteria versus mammalian cells, or differences in the materials used in the various assays.…”
Section: Resultscontrasting
confidence: 40%
“…Interestingly, these truncated fusion proteins displayed a higher specific binding to PtdIns(3)P than to polyphosphorylated inositol lipids. On the other hand, our previous studies using the full-length HIP1 expressed in 293T cells indicated that its lipid-binding preference was polyphosphorylated 3-phosphoinositides (29). Our contradictory results may be due to either the absence of the carboxyl terminal end of the protein, differences in proteins expressed in bacteria versus mammalian cells, or differences in the materials used in the various assays.…”
Section: Resultscontrasting
confidence: 40%
“…The changes in cell morphology in the Hip1r knockdown cell studies suggested that Hip1r plays a global role in regulating actin and membrane dynamics. Furthermore, overexpression of both Hip1 and Hip1r has previously been shown to stabilize growth factor receptors on the cell surface (9). This is the putative mechanism of transformation by Hip1 when overexpressed in certain human cancers (6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is hypothesized that Hip1/R promote clathrin assembly by releasing LC's inhibition of lattice assembly (Chen and Brodsky, 2005;Legendre-Guillemin et al, 2005). Hip1 family members also interact with phosphatidyl-inositol lipid through an N-terminal ANTH domain and F-actin through a talin-Hip1/R/Sla2p actin-tethering C-terminal homology (THATCH) domain, suggesting that these proteins also serve to coordinate the actin cytoskeleton at clathrin-coated pits (McCann and Craig, 1997;Engqvist-Goldstein et al, 1999;Legendre-Guillemin et al, 2002;Hyun et al, 2004;Senetar et al, 2004;Sun et al, 2005).…”
Section: Introductionmentioning
confidence: 99%